2021
DOI: 10.1002/jsfa.11294
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Camellia sinensis fermentation end‐product (black tea) on retinal microvasculature: an updated OCTA analysis

Abstract: BACKGROUND: Tea, second only to water, is one of the most regularly consumed drinks in the world. Its potentially beneficial effects on general health may be enormously important. Optical coherence tomography angiography (OCTA) now allows clinicians to examine the acute retinal morphological changes caused by black tea consumption. The purpose of this study was to investigate the acute impacts of a Camellia sinensis fermentation end-product (black tea) on retinal microvasculature in healthy individuals using O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Clinical trials investigating the efficacy of GTE in various ophthalmic diseases have provided valuable insights into its potential therapeutic benefits ( Table 1 ). In a study by Doğan et al, it was observed that black tea consumption did not yield immediate effects on macular microcirculation in healthy individuals, suggesting limited impact on retinal vascular health [ 51 ]. However, other trials have shown more promising results.…”
Section: Therapeutic Uses In Eye Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials investigating the efficacy of GTE in various ophthalmic diseases have provided valuable insights into its potential therapeutic benefits ( Table 1 ). In a study by Doğan et al, it was observed that black tea consumption did not yield immediate effects on macular microcirculation in healthy individuals, suggesting limited impact on retinal vascular health [ 51 ]. However, other trials have shown more promising results.…”
Section: Therapeutic Uses In Eye Diseasesmentioning
confidence: 99%
“… ophthalmic disease number of participants intervention final effect reference retinal microvasculature 60 black tea (2 mg/250 mL water) Black tea consumption did not have any immediate effect on macular microcirculation in healthy individuals. [ 51 ] glaucoma 43 GTE and EGCG extract (capsule 400 mg) Individuals with elevated intraocular pressure or risk factors for glaucoma development may benefit from moderate consumption of GT or its concentrated extracts. [ 52 ] dry eye and meibomian gland dysfunction (MGD) 60 topical GTE (1 mg/5 mL distilled water) Topical application of GTE is a safe, effective, and well-tolerated treatment option for mild to moderate evaporative dry eyes and meibomian gland dysfunction.…”
Section: Therapeutic Uses In Eye Diseasesmentioning
confidence: 99%